Reconocimiento de Saberes Tradicionales en Salud. Andes, Antioquia 2019: Aproximación Cualitativa. - Jaramillo Delgado, Gonzalo Hernando; Agudelo Arias, Mariana; Jaramillo Vargas, Juliana; Moreno Villa, Francia Elena (Revista Cuidarte)
Introduction: revaluing and re-signifying the identity of traditional health knowledge is challenging in a culture mediated by industrialization, surviving with a historical past, cultural and symbolic heritage, from a mixed identity that is conjugated in a territorial syncretism, which persists through physical and cultural traces of magical-religious traditions. Objective: to recognize the ethnographic particularities of the agents who carry popular knowledge in health that allows them to strengthen their practices in the Andes-Antioquia municipality. To re-signify these practices to recover their identity and symbolic ritual environments, in the configuration of their identity as an organic body in social spaces. Methodology: qualitative, descriptive type research, with ethnographic perspective (micro-ethnographic), systematized through in-depth interviews, accompanied by photographic records and participant observations. Results: 48 social agents between 30 and 70 years old, most of them settled in rural areas, were identified. Among them: sobanderos with secret, sobanderos with pain or componedores, hierbateros and rezanderos. Their diverse identity is recognized from a magical religious emergence and the characteristics of their inherited knowledge are exposed, in an enveloping rituality that recreates and vitalizes them in social spaces. Discussion: the results are analyzed within the framework of social, multidimensional and complex spaces, through its three elements: social structures, social relations and spatial forms. Conclusions: spatial forms transfer symbolism to the physical social space with characteristics that strengthen the exercise of their knowledge and identity. The gap between western knowledge and traditional knowledge is closing more and more due to the strength of its realities in the daily life of a globalized society.